2015
DOI: 10.18044/medinform.201521.131
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomaviruses, Herpes Viruses and Oral Neoplasms

Abstract: Human papillomaviruses constitute the most widely spread sexually transmitted viral infection world-wide. In about 1% of the cases, a continuing HPV infection can lead to the appearance of precancerous conditions. In a subsequent carcinoma progression, different types of cancer can develop -cervical, rectal, penile, oral, throat, laryngeal, etc. More than 200 HPV types have been established, with at least 25 found in lesions in the oral cavity.The attention of specialists in the field has been focused on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…This hypothesis is backed by the fact that various amounts of virus genomes are frequently detected in tumour cells. Some viruses such as HPV (human papillomavirus) are carcinogenic in themselves, while others such as EBV (Epstein-Barr virus), HSV (herpes simplex virus) simply accelerate the progression of existing cancer (19).…”
Section: Oncogenic Virusesmentioning
confidence: 99%
“…This hypothesis is backed by the fact that various amounts of virus genomes are frequently detected in tumour cells. Some viruses such as HPV (human papillomavirus) are carcinogenic in themselves, while others such as EBV (Epstein-Barr virus), HSV (herpes simplex virus) simply accelerate the progression of existing cancer (19).…”
Section: Oncogenic Virusesmentioning
confidence: 99%
“…Although papillomaviruses were poorly studied in the 1950s and 1960s, this period is associated with some important advances, including physicochemical analysis of the virion and the demonstration that HPV replication is associated with the process of differentiation of the infected epithelium [ 2 ]. The advent of molecular cloning in the 1970s initiated more extensive research and provided opportunities for its mapping, sequencing, and in-depth study of the structure and functions of viruses [ 3 ]. Bovine papillomavirus type 1 (BPV1) is a standard model for conducting these studies because the virus induces focal transformation of established rodent cell lines [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Syrjanen, nearly 80% of women are at risk for HPV infection. This is not the case with regard to affecting the oral epithelium; for example, in the United States, it has been found that 7% of people aged 14–69 years are infected with HPV, and the infection in men is almost three times more common [ 3 ]. The majority of HPV infections in men are thought to be transitory and asymptomatic, with no clinical manifestations [ 10 ].…”
Section: Introductionmentioning
confidence: 99%